Reassessing Human Rights Protection and R2P in Southeast Asia: A Contextual Analysis of ASEAN’s Non-Intervention Doctrine and Institutional Limitations - Fitriyah, Aidatul; Hamdan, Ahmad Harith Irfan bin (Sinergi International Journal of Law, 2025)
This study aims to examine the structural gap between ASEAN’s rhetorical commitment to the Responsibility to Protect (R2P) and its practical implementation in Southeast Asia, particularly in addressing large-scale human rights violations. Using a qualitative research design, the study adopts a systematic and contextually grounded literature review method, integrating normative analysis and empirical case studies to assess how R2P is interpreted, contested, and operationalized within ASEAN’s legal-political frameworks. Data were sourced from peer-reviewed publications, legal documents, and institutional reports, and analyzed using contextual analysis and thematic coding. The findings reveal that despite formal support for R2P as articulated in the 2005 World Summit Outcome Document, ASEAN’s operational response to humanitarian crises, such as the Rohingya genocide in Myanmar and the prolonged conflict in Papua, Indonesia, remains limited, symbolic, and diplomatically cautious. The region’s deep-rooted adherence to the principle of non-intervention, along with consensus-based decision-making and institutional inertia, has significantly constrained ASEAN’s ability to fulfill the third pillar of R2P: the international responsibility to act when a state fails to protect its population. This study concludes that effective implementation of R2P in Southeast Asia requires not only normative commitment but also institutional transformation. This includes redefining the principle of non-intervention, strengthening the mandate of ASEAN’s human rights mechanisms such as AICHR, and developing coordinated post-intervention strategies that involve local and regional actors. The significance of this research lies in its contribution to both scholarship and policy. It offers a region-specific, norm localization perspective on R2P, addressing gaps in the existing literature that often overlook Southeast Asia’s unique normative context. At the same time, it provides practical insights for reforming ASEAN’s institutional architecture to enable more responsive, legitimate, and context-sensitive humanitarian action.